Digital games and physical rehabilitation of low back pain : A comparative analysis of commercial vs. serious game - Ranta, Joni (My University, 2025)
Interest in gamification in rehabilitation has grown due to low adherence to traditional therapy, rising healthcare costs, and uneven access to resources. In general, studies highlight the potential of gamification compared to traditional physical therapy or home exercise, with results that are either similar or superior. Previous studies have used two types of games, commercial and serious games. The aim of this thesis is to examine the differences between these games in the physical rehabilitation of low back pain, which is one of the leading causes of disability worldwide, and to explore from the perspective of games why they are not commonly used in its rehabilitation. The games chosen for this thesis were based on observations of previous studies which have shown rehabilitation games generally lacking entertainment features, while commercial games are missing essential components for rehabilitation effectiveness. As Nintendo has been utilizing physical movements in their prior games, it was chosen to represent the commercial game and serve as a reference point as a state-of-the-art digital game with their game Ring Fit Adventure. Valedo Motion developed specially for patients with low back pain was chosen to represent the serious game. The games were compared based on technology, user engagement strategies, adaptability, customization and progression in relevance to low back pain rehabilitation. Analysis of these games show that while both games may pursue the same goal, the interaction between the user and the game can differ significantly. This in turn places limitations on the game’s implementation. Aesthetically, the games are not far apart, but the richer gameplay experience offered by Ring Fit Adventure shows how the collaboration between health experts and a major game company has produced a successful gaming experience that also considers individual characteristics that have often been criticized of missing in commercial games. Valedo Motion is a bit more limited from interaction perspective but can be justified based on the chosen approach of measuring trunk and pelvis movements with two attachable body sensors which produce decent gameplay with limited content. The results show rapid development of the gaming industry, including serious games. However, while Valedo Motion has been studied in several cases demonstrating its usefulness in low back pain physical therapy, the lack of recent information and announcements about the product raises questions. Commercial games can be sold to a larger segment, while for serious games the business is more complex with addressing specific problems with more diverse target audience. Unleashing the full potential of serious games requires multidisciplinary expertise in development but also understanding of game fundamentals to be able to adapt these solutions effectively in the interventions.
Keywords: digital games, serious games, physical rehabilitation, low back pain